Speaking right: HRDs role in mediating good boardroom conversations. Issue 2 (11th December 2019) - Beech, Nick; Gold, Jeff; Beech, Susan; Auty, Tricia
Abstract : Purpose: This paper aims to explore the impact discourse has on decision making practices within the boardroom and considers how personal proficiency in micro-language use can enhance an individual's personal efficacy in influencing boardroom decisions. The work uses Habermas' theory of communicative action to critique board talk, highlighting the need for greater understanding of the power of everyday taken for granted talk in strategy shaping. It illuminates the contribution that human resource development (HRD) professionals can make to the management of such behaviour and minimising dysfunctional behaviour and enabling effective boardroom practices. Design/methodology/approach: Traditional governance theory from a business and organisational perspectives are provided before considering the boardroom environment and HRD's role. The authors undertake ethnographic research supported by conversation analysis to explore how directors use talk-based interpersonal routines to influence boardroom processes and enact collective decision making. The authors provide one extract of directors' talk to illustrate the process and demonstrate what the data "looks like" and the insights it holds. Findings: The analysis suggests that the established underlying assumptions and rationale ideologies of corporate governance are misplaced and to understand the workings of corporate governance HRD academics and professionals need to gain deeper insight into the employment of talk within boards. Armed with such insights HRD professionals can become more effective in developing strategies to address dysfunctional leadership and promote good governance practice throughout their organisation. Social implications: The work raises a call for HRD to embrace a societal mediation role to help boards to become a catalyst for setting good practice which is strategically aligned throughout the organisation. Such roles require a more dialogical, strategic and critical approach to HRD, and professionals and academics take a more holistic approach to leadership development. Originality/value: The paper considers the role of the development of HRD interventions that both help individuals to work more effectively within a boardroom environment and support development to shape a boardroom culture that promotes effective governance practice by influencing boardroom practice thereby promoting strong governance and broad social compliance throughout the organisation.